2021
DOI: 10.1088/1475-7516/2021/04/036
|View full text |Cite
|
Sign up to set email alerts
|

Bumblebee gravity and particle motion in Snyder noncommutative spacetime structures

Abstract: A metric with a Lorentz violating parameter is associated with the bumblebee gravity model. We study the motion of a particle in this bumblebee background where the dynamical variables satisfy non-canonical Snyder algebra along with some critical survey on the classical observations in the bumblebee background to see how these would likely differ from Schwarzschild background. It has been found that the perihelion shift acquires a generalized expression with two independent parameters. One of these two is conn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…This study also explored three classical tests viz., the advance of perihelion, bending of light and Shapiro's time delay, and showed that corrections from Lorentz violation were present even in the absence of a massive gravitational source and the Lorentz violation background deforms the spacetime. In another study, particle motion in Snyder noncommutative spacetime structures was studied in the presence of Lorentz violation [13].…”
Section: Introductionmentioning
confidence: 99%
“…This study also explored three classical tests viz., the advance of perihelion, bending of light and Shapiro's time delay, and showed that corrections from Lorentz violation were present even in the absence of a massive gravitational source and the Lorentz violation background deforms the spacetime. In another study, particle motion in Snyder noncommutative spacetime structures was studied in the presence of Lorentz violation [13].…”
Section: Introductionmentioning
confidence: 99%
“…and C l are the complex numbers which can be found according to the boundary condition in equation (13). In figures 4 and 5, the transmission and reflection coefficients are displayed, respectively, for various values of the Lorentz-violating parameter and multipole numbers.…”
Section: The Wkb Methodsmentioning
confidence: 99%
“…However, despite the non-Riemannian background, most studies in bumblebee gravity, for example, have been conducted within the metric approach of gravity, where the metric is the only dynamical geometric field. These investigations focus on obtaining exact solutions for different models that incorporate LSB in curved spacetimes, including bumblebee gravity [6][7][8][9][10][11][12][13], parity-violating models [14][15][16][17][18], and Chern-Simons modified gravity [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These solutions allow to study various aspects of the role of spontaneously LSB on the physics of compact objects, such as black holes and wormholes (e.g, see Refs. [28][29][30][31][32][33][34][35][36][37][38][39]). It would be interesting to mention that the study of causality in Lorentz-violating models is a relevant topic.…”
Section: Introductionmentioning
confidence: 99%